The development of a textbook using Dick and Carey Instructional Model and Carey model to improve fluently speaking skill (Development and experimental study on the students of Sains Al-Quran University (UNSIQ) in Central Java Indonesia) - Sunarko, Asep; Abdulbasit; Latif, Faozi (Journal of Educational and Psychological Sciences, 2020)
The aims of this research are the results of the developing textbooks with a Dick, Carey and Carey Development model, and to know the effectiveness of the textbook in terms of improving the fluency and the correct pronunciation’s students in speaking Arabic orally. This research is development research which is using a qualitative and a quantitative approach. The development procedures in this research are divided into three stages: teaching material designing, validation of expert (the contents and the design expert), and field test is the last stage. The result of this research is (1) that the textbook with dick, carey and carey Development model (2) the textbook with Dick, Carey and Carey Development model is effective to accelerate the fluency of students. It can be seen from the T-test that is bigger than the standard of value which is 10.12 >1, 72. For that, depending on the calculation of the last result, the aforementioned hypothesis is acceptable or effective.